2019
DOI: 10.3390/toxins11040191
|View full text |Cite
|
Sign up to set email alerts
|

First Characterization of The Venom from Apis mellifera syriaca, A Honeybee from The Middle East Region

Abstract: Bee venom is a mixture of several components with proven therapeutic benefits, among which are anti-inflammatory, analgesic, and various cardiovascular conditions. In this work, we analyzed for the first time the proteomic content and biological properties of the crude venom from Apis mellifera syriaca, a honeybee from the Middle East region. Using high-performance liquid chromatography-tandem mass spectrometry, we evidence the venom contains phospholipase A2, hyaluronidase, mast cell-degranulating peptide, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 35 publications
1
37
1
Order By: Relevance
“…Interestingly, its activity can be improved by melittin. This has been shown to occur during the process of erythrocyte lysis, proving the presence of synergistic action between both bvPLA 2 and melittin [36,37]. In fact, it has been demonstrated that melittin helps in exposing membrane phospholipids to the catalytic site of enzymes via opening melittin-induced channels [38].…”
Section: Main Compounds Of Bee Venommentioning
confidence: 99%
“…Interestingly, its activity can be improved by melittin. This has been shown to occur during the process of erythrocyte lysis, proving the presence of synergistic action between both bvPLA 2 and melittin [36,37]. In fact, it has been demonstrated that melittin helps in exposing membrane phospholipids to the catalytic site of enzymes via opening melittin-induced channels [38].…”
Section: Main Compounds Of Bee Venommentioning
confidence: 99%
“…Bee venom contains several biologically active molecules such as peptides, bioactive amines and enzymes, which have an advantageous potential in healing the wounds. Bee venom contains different peptides including melittin, apamin, adolapin, secapin and its isomers (i.e., secapin-1 and -2), procamine, tertiapin and mast cell degranulating peptide (MCD-peptides) [ 22 , 23 ].…”
Section: Chemical Composition Of Bee Venommentioning
confidence: 99%
“…Venomous animals have been a focus of interest for humans for years due to the danger associated with them and the possibility of taking advantage of venom action and utilizing it in medicine [1,2]. Animal venoms are immensely complex mixtures composed of proteins, peptides, biogenic amines, and other substances of low-molecular weight, which are often enzymatically active [3,4,5]. Especially, the great interest is related to the biological activity of proteins isolated from bee (melittin, apamina and tertiapin) and wasp (mastoparan and bradykinin) venoms [2].…”
Section: Introductionmentioning
confidence: 99%